Nk6, a novel Drosophila homeobox gene regulated by vnd. - Uhler, J.; Garbern, J.; Yang, L.; Kamholz, J.; Mellerick, D.M. (Mechanisms of Development, 2002)
Nk(x)-type homeobox genes are an evolutionarily conserved family that regulate diverse developmental processes. Here we describe a novel Drosophila gene, Nk6, which encodes an Nk-type transcription factor most homologous to vertebrate Nkx6.1 and Nkx6.2. The homeodomains and NK decapeptide domains of all three proteins are highly conserved. Nk6 is expressed in the embryonic brain, ventral nerve cord, hindgut, and internal head structures. Nerve cord expression is in midline precursors, several ventral and intermediate column neuroblasts, and later in neurons but not glia, similar to the known expression of Nkx6 genes in the neural tube. We show genetically that Nk6 is positively regulated, directly or indirectly, by vnd in brain precursors. In vnd mutants, head neuroectoderm Nk6 expression is abolished where it is normally co-expressed with vnd. Conversely, vnd-overexpression leads to ectopic Nk6 expression in the brain. These findings further highlight the importance of interactions between Nk(x)-type genes in regulating their expression.